Vitamin D Status in Diabetes Mellitus: Comparison Between Outpatients and Inpatients - Pellegrino M; Castellano E; Garino F; Tassone F; Gianotti L; Visconti GL; Attanasio R; Borretta G (Journal of Preventive Medicine And Care, 2017)
Objectives: Vitamin D (25(OH)D) status has been extensively evaluated in different populations and care settings. A negative relationship between glycated hemoglobin (HbA1c) and serum 25(OH)D levels in outpatients with diabetes has been reported, while data about 25(OH)D status in inpatients with diabetes are inconsistent. The aim of the study was to evaluate 25(OH)D levels in a large series of inpatients with type 1 and type 2 diabetes and in an age-, sex-, serum creatinine-, and HbA1c-matched group of outpatients with diabetes. Design: After the preliminary exclusion of patients with confounding factors, 540 subjects with diabetes were retrospectively evaluated in a 1:1 matched case-control study between inpatients and outpatients. Results: 25(OH)D levels resulted significantly lower in inpatients versus outpatients with diabetes (37.9 nmol/L, median, 25.3 interquartile range, vs 44.9, 31.8 nmol/L, respectively), regardless of season. 25(OH)D levels were inversely correlated with HbA1c levels and BMI in outpatients, and with fibrinogen and erythrocyte sedimentation rate in inpatients. Conclusions: Vitamin D deficiency is common in diabetic inpatients and more frequent than in diabetic outpatients. 25(OH)D status in diabetic inpatients is not related to glycemic control but is likely influenced by acute inflammatory condition.
Keywords: diabetes mellitus